2019
DOI: 10.4018/ijide.2019010103
|View full text |Cite
|
Sign up to set email alerts
|

New Discoveries for User Acceptance of E-Learning Analytics Recommender Systems in Saudi Arabia

Abstract: This article adopts e-learning analytics principles to provide a new model to explain the acceptance behaviour of recommender systems adoption with e-learning in the Saudi Arabian context and reflects the increasing focus of the Saudi Arabian Ministry of Education on delivering online educational services. This focus has come at the necessity to improve overall access to the education system, and higher education and has been driven with evidence of improving learning outcomes with electronic learning (e-learn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…This study differs from prior studies in the following respects: To begin, this research will incorporate an integrated TAM model of EDQ and social influence into the usage of e-learning. Second, in contrast to other studies in Saudi Arabia, such as Rajab (2018) , Alshehri et al (2019) , and Alharbi and Sandhu (2019) , this study aims to support a comprehensive review of current articles in the field of e-learning. Third, unlike earlier research that has focused just on the intention to use, this study investigates the impact of many factors on students’ attitudes toward and satisfaction with using an e-learning system.…”
Section: Discussionmentioning
confidence: 99%
“…This study differs from prior studies in the following respects: To begin, this research will incorporate an integrated TAM model of EDQ and social influence into the usage of e-learning. Second, in contrast to other studies in Saudi Arabia, such as Rajab (2018) , Alshehri et al (2019) , and Alharbi and Sandhu (2019) , this study aims to support a comprehensive review of current articles in the field of e-learning. Third, unlike earlier research that has focused just on the intention to use, this study investigates the impact of many factors on students’ attitudes toward and satisfaction with using an e-learning system.…”
Section: Discussionmentioning
confidence: 99%
“…The results indicated that infrastructure and technology decisions made during the implementation process were important in motivating students to use and accept e-learning systems. Abdullah and Ward [15] also investigated factors influencing e-learning acceptance using TAM. Their findings revealed that self-efficacy, subjective norms, enjoyment, anxiety and experience with using computers had a significant effect on students' acceptance of e-learning.…”
Section: Related Studies On the Factors Impacting The Adoption And Usage Of Elearning Systemsmentioning
confidence: 99%